Two-in-One Chemogene Assembled from Drug-Integrated Antisense Oligonucleotides To Reverse Chemoresistance - Mou, Quanbing; Ma, Yuan; Ding, Fei; Gao, Xihui; Yan, Deyue; Zhu, Xinyuan; Zhang, Chuan (Journal of the American Chemical Society, 2019)
Combinatorial chemo and gene therapy provides a promising way to cure drug-resistant cancer, since the codelivered functional nucleic acids can regulate drug resistance genes, thus restoring sensitivity of the cells to chemotherapeutics. However, the dramatic chemical and physical differences between chemotherapeutics and nucleic acids greatly hinder the design and construction of an ideal drug delivery system (DDS) to achieve synergistic antitumor effects. Herein, we report a novel approach to synthesize a nanosized DDS using drug-integrated DNA with antisense sequences (termed “chemogene”) to treat drug-resistant cancer. As a proof of concept, floxuridine (F), a typical nucleoside analog antitumor drug, was incorporated in the antisense sequence in the place of thymine (T) based on their structural similarity. After conjugation with polycaprolactone, a spherical nucleic acid (SNA)-like two-in-one chemogene can be self-assembled, which possesses the capabilities of rapid cell entry without the need for a transfection agent, efficient downregulation of drug resistance genes, and chronic release of chemotherapeutics for treating the drug-resistant tumors in both subcutaneous and orthotopic liver transplantation mouse models.